Hormonal, biochemical, and hematological study of horses used in police patrol in an equatorial climate - Suelen Andrade Ricarte; Misael Brito de Lima; Cleberson Eduardo Santos de Oliveira; Osvaldo Gato Nunes Neto; Antônio Humberto Hamad Minervino; Rejane Santos Sousa; Luís Fernando Gouvêa; Alanna do Socorro Lima da Silva; Ana Izabel Passarella Teixeira; Adriana Caroprezo Morini (Pubvet)
This study aimed to evaluate cortisol secretion and biochemical and hematological parameters in police patrol horses in order to evaluate how patrolling stress could alter these parameters. The sample consisted of ten healthy male adult horses. Blood collection occurred before and after patrols, as well as 24 and 31 hours after the first patrol. The analyses included cortisol levels and secretion, lactate, lactate dehydrogenase, creatine and kinase rates, as well as red and white blood cell counts. Results showed no significant changes in cortisol concentrations but indicated a reduced circadian rhythm. Biochemical variables such as lactate, lactate dehydrogenase and creatine kinase were within reference values. Hematological parameters showed an altered neutrophil/lymphocyte ratio during the entire sampling period, with values below the ideal reference. In conclusion, urban patrolling did not cause temporary changes in the evaluated parameters, suggesting that the animals are adapted to this activity and that rest time is adequate. However, alterations in cortisol circadian rhythm rate and neutrophil:lymphocyte ratio indicate potential chronic wear on the well-being of these animals.